Synthesis of highly substituted 3-formylfurans by a gold(I)-catalyzed oxidation/1,2-alkynyl migration/cyclization cascade - Wang, Tao; Shi, Shuai; Hansmann, Max M.; Rettenmeier, Eva; Rudolph, Matthias; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2014)
3-Formylfuran derivatives are core structures of a variety of bioactive natural products. However, procedures for their preparation are still rare and generally inefficient in terms of atom economy: These methods require multiple steps or harsh reaction conditions and show selectivity problems. An efficient gold(I)-catalyzed cascade reaction that leads to 3-formylfurans from easily accessible starting materials is now described. A wide variety of 3-formylfurans were obtained from the corresponding symmetric and unsymmetric 1,4-diyn-3-ols in the presence of an N-oxide in good to excellent yields. Isotope-labeling experiments as well as DFT calculations support a mechanism in which, after an initial oxygen transfer, a 1,2-alkynyl migration is favored over a hydride shift; a cyclization ensues to afford the desired functionalized furan core.
Gesehen am 29.07.2020